Urinary microbiota; Which non‐ınvasive urine collection method should we use?. Issue 7 (12th April 2021) - Ozer, Muhammed Selcuk; Yildiz, Huseyin Alperen; Incir, Canet; Deger, Muslim Dogan; Bozkurt, Ozan; Ergor, Gul; Tuncok, Yesim; Esen, Nuran; Esen, Ahmet Adil
Abstract: Objective: The aim of this study is to establish the optimal non‐invasive urine sample collection method for the microbiota studies. Methodology: Twelve men with bladder carcinoma underwent first voided and midstream urine collection. Urine samples were analysed using V3‐V4 regions of bacterial 16s ribosomal RNAs. Bacterial groups with relative abundance above 1% were analysed in first voided urine and midstream urine samples at phylum, class, order and family level. At the genus level, all of the identified bacterial groups' relative abundances were analysed. The statistical significance ( P < .05) of differences between first voided and midstream urine sample microbiota was evaluated using the Wilcoxon test. Results: According to the analysis, 8 phyla, 14 class, 23 orders, 39 families and 29 different genera were identified in the first voided and the midstream urine samples. Statistical differences were not identified between first voided and midstream urine samples of all bacteria groups except the Clostridiales at order level (p:0.04) and Clostridia at class level ( P : .04). Conclusions: Either first voided or midstream urine samples can be used in urinary microbiota studies as we determined that there is no statistically significant difference between them regarding the results of 16s ribosomal RNA analysis.